Pengaruh Fasilitas Dan Kualitas Pelayanan Terhadap Kepuasan Pengunjung Pada Unit Pengelola Taman Margasatwa Ragunan Tahun 2022 - Islah, Khikmatul; Haryani, Tri (Lembaga Layanan Pendidikan Tinggi Wilayah III DKI Jakarta, 2023)
The number of visitors who came to Ragunan has declined significantly every year. The number of visitors there was the highest in 2019 (5.401.907 visitors). Problems that often arise are visitors complaining about a barcode or QR code being delivered slowly or not being sent to online registration to visit a Ragunan management unit during online registration, and visitors complaining about the difficulty of calling the Ragunan management unit call center. This would have an impact on visitors' dissatisfaction with the quality of services that are offered on a Ragunan. This zoo study seeks to comprehend the impact of facilities and the service quality management unit on visitor satisfaction in 2022 at the Ragunan Zoo. This study used a quantitative approach and provided an explanation. The population in this study will be people or visitors to Ragunan Zoo in 2022, as many as 950.552 people, using a formula obtained from 100 Slovene samples. Sampling techniques called for purposive sampling. The questionnaire was used to collect data, and the data was analyzed using multiple regression analysis techniques. The findings revealed that facilities have some positive effects on visitor satisfaction. Although service quality has some positive effects, it has not significantly increased visitor satisfaction. The facilities and the quality of services provided have some positive effects and are important to the satisfaction of visitors to the Ragunan management unit at the same time